Management of hepatitis B during pregnancy. (11th February 2016) - Kar, Premashis; Mishra, Saurabh
ABSTRACT: Introduction : Women of childbearing age or who are pregnant and have hepatitis B infection require specialized management both during and after pregnancy. Effective maternal screening along with judicious use of available antivirals and immunoprophylaxis greatly reduces the perinatal transmission of hepatitis B virus (HBV) and dramatically declines the incidence and prevalence of chronic hepatitis B and its sequelae. Areas c overed : A systematic literature search was done using Embase, Medline and Cochrane library from January 1990 to July 2015 and appropriate articles selected for this review. This review highlights the timing of therapy, choice of antiviral agent along with passive and active immunoprophylaxis for infants. Issues regarding breastfeeding in HBV-infected women and who are on antiviral therapy are addressed. Expert o pinion : All decisions about starting, continuing or stopping antiviral therapy must consider maternal and fetal risks. Antiviral therapy during the third trimester of pregnancy in women with active disease reduces the risk of perinatal transmission. Safety data in pregnancy are mostly available for lamivudine and tenofovir. However, recent studies have also advocated use of telbivudine in such patients. Detailed discussion with the patient regarding the risks and beneﬁts of therapy is very important. Prophylaxis remains the best method of prevention of perinatal transmission.